What can the G7 do to achieve the Global Health 2035 goals? - Gavin Yamey; Sara Fewer; Sabine Campe (Kiel Institute for the World Economy (IfW), 2015)
The Global Health 2035 report shows that there is tremendous potential to achieve dramatic gains in global health over the next 20 years, particularly with regards to the G7's priorities of eliminating NTDs, preparing effectively for pandemics, and tackling AMR. These challenges require urgent international collective action and demand the leadership and focused investment of the G7. To maximize its impact and help mobilize action for the post-2015 health agenda, the G7 should target its efforts towards four critical policy options: investing in new tools, supporting policy and implementation research, strengthening national health systems, and fostering global coordination. By working in partnership with donor, low- and middle-income countries on these policy options, the G7 can set the course to achieve a grand convergence in global health.
Keywords: 330